2021
DOI: 10.1155/2021/6815713
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rh2 Suppresses Metastasis and Growth of Colon Cancer via miR-491

Abstract: Ginsenoside Rh2 is considered as a new direction for future cancer treatment because of its excellent anticancer effect. However, due to its low bioavailability, it cannot exert its significant anticancer effect when applied directly to the human body. Chitosan (CS), a nanomaterial, has been verified to be able to enhance drug efficacy via its coating for drugs. Thus, we designed this study to investigate the impact of CS-coated ginsenoside Rh2 on the metastasis and growth of colon cancer (CC). First, ginsenos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Moreover, as demonstrated by several studies, decreased miR-491-3p was exhibited in gastric cancer specimen as compared with the normal tissue [ 17 , 25 ], being consistent with our clinical results. In a previous study, ginsenoside Rh2, an anticancer nutrient, did lower the activity of colon cancer cells, and under its intervention, the cells presented dysregulation of miR-491-3p and metastasis activities [ 26 ]. In addition, miR-491-3p was overexpressed in noncancerous tissues compared with its expression in papillary thyroid cancer (PTC) tissues, which inhibited PTC cell migration and invasion possibly via targeting NEAT1_2 and TGM2 [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as demonstrated by several studies, decreased miR-491-3p was exhibited in gastric cancer specimen as compared with the normal tissue [ 17 , 25 ], being consistent with our clinical results. In a previous study, ginsenoside Rh2, an anticancer nutrient, did lower the activity of colon cancer cells, and under its intervention, the cells presented dysregulation of miR-491-3p and metastasis activities [ 26 ]. In addition, miR-491-3p was overexpressed in noncancerous tissues compared with its expression in papillary thyroid cancer (PTC) tissues, which inhibited PTC cell migration and invasion possibly via targeting NEAT1_2 and TGM2 [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a new type of programmed cell death, apoptosis has been confirmed to participate in the pathogenesis and progression of AMI by regulating the inflammatory response and stimulating the release of proinflammatory factors, but the exact mechanism has not yet been clearly elucidated [15]. Rh2, the main active component of ginseng, has shown excellent effects in multiple pathological improvements, such as antitumor, antiallergy, antiinflammation, enhancing immunity, and resisting hypoxia, in addition to a certain protective role in CVD [16][17][18][19]. erefore, this paper intends to verify in vivo whether Rh2 can exert anti-inflammatory action by regulating CM pyroptosis in AMI rats, thus alleviating myocardial injury and providing a reliable theoretical basis for future treatment of AMI.…”
Section: Discussionmentioning
confidence: 99%
“…found that ginsenoside Rh2 induces the death of CRC cells and inhibits cancer cell migration by activating NF- κ B transcriptional activity ( Li et al, 2011 ). Rh2 induces the expression of miR491 to inhibit the metastasis of CRC cells ( Wei et al, 2021 ). Ginsenoside Rg3 and 5-fluorouracil combined treatment of CRC cells enhances the anti-tumor effect of 5-fluorouracil in CRC cells and inhibits tumor invasion and migration through the PI3K/AKT pathway ( Sun et al, 2017 ; Liu et al, 2022 ).…”
Section: Ginsenosides Change the Basic Hallmarks Of Crc Cellsmentioning
confidence: 99%